Occupational accidents and injuries among workers in the construction industry of Windhoek, Namibia - Nghitanwa, Emma Maano; Lindiwe, Zungu (International Journal of Health, 2017)
The construction industry is the most dangerous industry in the word with higher prevalence of occupational accidents, injuries and diseases. There is a paucity of studies that investigate occupational accidents, injuries and diseases in the Namibian construction industry. The study was conducted to determine the magnitude of occupational accidents, injuries and diseases in the construction industry of Windhoek, Namibia. A quantitative, retrospective document review was conducted to investigate the documents for reported occupational accidents, injuries and diseases for the period of five years, from April 2011 to March 2016. Data was analysed with SPSS version 23. The study found out that occupational accidents and injuries are prevalent in the Windhoek construction industry. The study recorded the total of 37 cases of occupational accidents and injuries. Young, male construction workers are mostly sustained accidents and injuries. Labourers were mostly affected than other occupations while cut by machinery comprise the majority of the source of accidents. The most body part injured is the general body. The researchers did not find any documentation for reported occupational diseases from the construction industry of Windhoek. The researchers recommended the preventive measures to be implemented to prevent occupational accidents and injuries and enforcement of legislations on occupational accidents, injuries and diseases recording and reporting.